Implementasi Laporan Penyelenggaraan Pemerintahan Daerah (LPPD) Tahun 2022 Pada Bagian Tata Pemerintahan Sekretariat Daerah Kabupaten Sumenep (Soetomo Magister Ilmu Administrasi, 2023)
The implementation in the preparation of the Sumenep District LPPD in terms of the commitment of OPD leaders was still less than optimal. In addition, based on the results of the research, the provision of facilities and infrastructure in the preparation of the Sumenep District LPPD has been allocated and implemented and there are still shortcomings in the form of lack of computer facilities and others. Staff involvement in its preparation exceeds the allocation of assigned staff. The use of facilities and infrastructure is optimized according to the ability of the Sumenep district government. Various obstacles were encountered in the preparation of the LPPD, ranging from lack of leadership commitment to duplication of similar reports. Key words: Implementation, LPPD, effective, efficient